Determinants of Auditor Reputation, Audit Committee, Audit Delay and Audit Fee on Audit Quality - Viona Permata Putri; Muhammad Abdul Aris (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the determinants of audit quality in consumer goods manufacturing companies listed on the Indonesia Stock Exchange between 2019 and 2023. Using a descriptive quantitative method and purposive sampling, secondary data were collected from annual reports and analyzed with logistic regression to examine the effects of auditor reputation, audit committee composition, audit delay, and audit fee on audit quality, measured by whether a Big Four auditor audits a firm. The results indicate that auditor reputation, proxied by the number of partners in the audit firm, does not significantly affect audit quality. In contrast, the audit committee significantly enhances audit quality, highlighting the importance of effective oversight in audit processes. Audit delay shows no significant impact, suggesting that the timing of audit completion is not a direct indicator of audit quality. Meanwhile, audit fees positively influence audit quality, as adequate fees allow auditors to perform more thorough and reliable audits. These findings emphasize the critical roles of audit committee effectiveness and sufficient audit fees in maintaining high audit standards. Limitations of this study include its focus on a single industry sector, a limited observation period, and a narrow set of variables. Future research should expand the scope to other industries, lengthen the study duration, and include additional factors to deepen the understanding of audit quality determinants.